Frequency of micronuclei in erythrocytes with sequential Giemsa-orange acridine staining in the domestic cat (Felis domesticus) - Quero, Arnoldo A.M. (2018)
Domestic felines share the domestic environment with humans and have conditions that make them especially sensitive to genotoxic compounds, they are good candidates to be used as bioindicators in the biomonitoring of domestic environments. The objective of the study was to apply the micronucleus test in erythrocytes of domestic cats (Felis domesticus), and to evaluate them by Giemsa and fluorescent acridine orange (OA) stains carried out sequentially to identify the most suitable for this species. The micronucleus test was applied in peripheral blood erythrocytes of adult domestic cats, with and without signs of disease (total = 24). The frequencies of micronuclei detected with OA were 2 to 10-fold higher than those recorded with Giemsa (p<0.0001), without differences by age factor or health status. It is hypothesized that OA staining allowed the detection of micronuclei of smaller size than the Giemsa analysis. The observed frequency of micronuclei proposes the use of the domestic cat to perform biomonitoring on the effect of environmental genotoxics.